Populism as a Concept and the Challenge of U.S. History - Charles Postel (IdeAs)
This paper explores the viability of populism as both a historical category and a political concept. Its starting point is the historical example of the first mass political expression that formed under the name of populism, and that was the U.S. People's Party of the 1890s. Although it carried the nickname of the Populist Party, this had virtually none of the meanings that were attached to the term populism at a later date. Historical populism in the U.S. was a farmer-labor movement that corresponded to labor and social-democratic movements across the late 19th -century capitalist world. This poses the challenge: is populism a capacious enough concept to include the U.S. historical precedent? Or does including the U.S. precedent render the category and concept toothless or even useless?